Biodegradation of spent engine oil by bacteria isolated from the rhizosphere of legumes grown in contaminated soil - Ismail, HY; Ijah, UJJ; Riskuwa, ML; Allamin, II (International Journal of Environment, 2014)
Biodegradation of spent engine oil (SEO) by bacteria isolated from the rhizosphere of Cajan cajan and Lablab purpureus was investigated. It was with a view to determining most efficient bacterial species that could degrade SEO in phytoremediation studies. Hydrocarbon degrading bacteria were isolated and identified by enrichment culture technique using oil agar supplemented with 0.1% v/v SEO. Total heterotrophic and oil utilizing bacterial count showed the occurrence of large number of bacteria predominantly in the rhizosphere soil, ranging between 54×108 - 144×108 CFU/g and 4×108- 96×108 CFU/g respectively. Percentage of oil utilizing bacteria ranged between 0% (uncontaminated non rhizosphere soil) to 76% (contaminated rhizosphere). Turbidimetrically, five bacterial species namely Pseudomonas putrefacience CR33, Klebsiella pneumonia CR23, Pseudomonas alcaligenes LR14, Klebsiella aerogenes CR21, and Bacillus coagulans CR31 were shown to grow maximally and degraded the oil at the rate of 68%, 62%, 59%, 58%and 45% respectively. Chromatographic analysis using GC-MS showed the presence of lower molecular weight hydrocarbons in the residual oil (indicating degradation) after 21 days, whereas the undegraded oil (control) had higher molecular weight hydrocarbons after the same period. The species isolated were shown to have high ability of SEO biodegradation and therefore could be important tools in ameliorating SEO contaminated soil. DOI: http://dx.doi.org/10.3126/ije.v3i2.10515 International Journal of the Environment Vol.3(2) 2014: 63-75